2004
DOI: 10.1016/j.top.2003.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Minimal atomic complexes

Abstract: Hu, Kriz and May recently reexamined ideas implicit in Priddy's elegant homotopy theoretic construction of the Brown-Peterson spectrum at a prime p. They discussed May's notions of nuclear complexes and of cores of spaces, spectra, and commutative S-algebras. Their most striking conclusions, due to Hu and Kriz, were negative: cores are not unique up to equivalence, and BP is not a core of M U considered as a commutative S-algebra, although it is a core of M U considered as a p-local spectrum. We investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…However, this co-H -structure is not necessarily co-associative and neither are the inclusion and projection maps necessarily co-H -maps. Furthermore, each Y i is minimal atomic in the sense of [5], and cannot be equivalent to a suspension except in the case i = p − 1 when it does desuspend [14].…”
Section: A P-local Splittingmentioning
confidence: 99%
“…However, this co-H -structure is not necessarily co-associative and neither are the inclusion and projection maps necessarily co-H -maps. Furthermore, each Y i is minimal atomic in the sense of [5], and cannot be equivalent to a suspension except in the case i = p − 1 when it does desuspend [14].…”
Section: A P-local Splittingmentioning
confidence: 99%
“…In [2,Theorem 3.3] it was shown that every p-local CW complex of finite-type is equivalent to a minimal one, so such minimal complexes exist in abundance.…”
Section: Minimal Atomic P-local Commutative S-algebrasmentioning
confidence: 99%
“…Proof The details follow from the proof of [2,Theorem 3.3], replacing ordinary homology with HAQ * (−), mutatis mutandis.…”
Section: Theorem 32 Let R Be P-local Cw Commutative S-algebra With mentioning
confidence: 99%
See 2 more Smart Citations